An investigation of hydrogen generation and antibacterial activity of TiO2 nanoparticles synthesized by the ionic liquid aided ionothermal method - Yadav, L.S. Reddy (H. : ĐHQGHN, 2018)
Amongst soft chemical synthetic routes, the ionothermal synthesis method (using an ionic liquid) has attracted research tremendously due to their remarkable features especially in the case of TiO2nano-particles synthesis. On the other hand, the significant role of TiO2 nanoparticles in the fields of photo-catalysis, photovoltaics, batteries etc. is noteworthy. Here, by considering these two remarkable aspects, TiO2 has been prepared by using an ionic liquid. The band gap of 3.2 eV has been determined through UV-Vis absorption spectra. The crystallite size was found to be 62 nm by PXRD. Additionally, TEM images have confirmed that the size of the particles is in the nanoscale. Furthermore, the significant properties of TiO2nanoparticles have been studied and utilized for photocatalytic water splitting, as well as for the development of antibacterial activities.